Study of potential probiotic and biotechnological properties of non-Saccharomyces yeasts from fruit Brazilian ecosystems - Fernández-Pacheco, Pilar; Rosa, Isabel Zaparoli [UNESP]; Arévalo-Villena, María; Gomes, Eleni [UNESP]; Pérez, Ana Briones (My University, 2021)
Yeast isolates from flowers and fruits from a Brazilian forest were studied. The yeasts were identified at species and strain level by PCR–RFLP and PCR-RAPD, respectively. The 46 isolated yeasts were classified into 11 different species belonging to the genera Candida, Diutina, Hanseniaspora, Meyerozyma, Pichia, Rhodotorula, and Torulaspora. A total of 20 different strains were found. In order to ascertain the probiotic potential, the resistance to gastrointestinal conditions, autoaggregation, and hydrophobicity assays were studied, along with the capacity to form biofilm. The results indicate that, although most of the strains presented better results than Saccharomyces boulardii (the only strain recognized as a probiotic yeast), four strains were the most promising, namely, Rhodotorula mucilaginosa 32, Meyerozyma caribbica 35, and Diutina rugosa 12 and 45, according to the Duncan test. Several biotechnological properties were evaluated. D. rugosa inhibited Dekkera bruxellensis. The assimilation or fermentation of seven sugars was tested, and only five of the yeasts did not show a capacity to assimilate any of the sugars under aerobic conditions. However, all strains were able to ferment at least one of the sugars under anaerobic conditions. As far as enzyme production is concerned, positive results were only found for the enzymes’ amylase, pectinase, and protease. D. rugosa 42 and Hanseniaspora opuntiae 18, followed of Pichia kluyveri 26, showed high values for the production of melatonin. In conclusion, the results of this study show that several non-Saccharomyces present probiotic characteristics, and these have good potential for industrial applications in the food or biotechnology industries. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Antimicrobial activity; Enzyme activity; Melatonin; Non-Saccharomyces; Probiotic yeasts